Numerical Modelling of Flood Inundation and Run-Up along the Banks of Pamba River, South West Coast of India - SS, Praveen; Babu, Veena Suresh; Vijayan, Aswathy; S, Sajith Babu (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 7 No 1 (2020): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2020)
The state of Kerala was in the shadow zone of several natural disasters. But the disasters which happened during the last two decades changed our perceptions and preconceived notions. Before two decades, for Keralites the term disaster was a matter of strange science fiction books, Hollywood cinemas or the things which were happening on the other side of the globe or planet. The tsunami of December 26, 2004, Ockhi of 2017, Kerala Floods of 2018 and its replicated version in 2019 exposed our vulnerabilities. During the event of 2018 Kerala Floods, the need for a Flood Warning System (FWS) in Kerala was badly felt. Though there are many components for a FWS, the main component of a FWS is the prediction of inundation and run-up along the banks of rivers/ water bodies. This component can only be accomplished through the process of numerical modelling. Numerical modelling is an efficient tool for estimating the past events and predicting the future ones. Through numerical modelling different scenarios of possible flood generating permutations and combinations will be carried out and hence in the event of a flood warning a closest matching will be picked from these, which will be subsequently used for mitigation. The results of numerical modelling will be the base for creating vulnerability maps which will be used for mitigation and rehabilitation. This investigation numerically simulates the possible flood rising inundation and run-up along the banks of Pamba River situated on the south west coast of India. The model results suggest that extreme rain fall events alone cannot inundate the banks of Pamba River, whereas external discharges emanating from dams, tidal reflections from the oceans etc. could inundate the terrain. The investigation also suggests several components for successfully establishing a flood warning system in Kerala with specific reference to Kerala floods 2018. How to cite this article: Praveen SS, Babu, Vijayan A et al. Numerical Modelling of Flood Inundation and Run-Up along the Banks of Pamba River, South West Coast of India. J Adv Res Alt Energ Env Eco 2020; 7(1): 8-14. DOI: https://doi.org/10.24321/2455.3093.202002